2018
DOI: 10.1590/0103-6440201801962
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth, Pacifier use and Breastfeeding: is there a Relationship?

Abstract: The immaturity of born to preterm infants may predispose to sucking difficulties. This research aimed to evaluate if pacifier use is associated with preterm birth and influenced in type of infant feeding. This comparative cross-sectional study was conducted in Belo Horizonte, Brazil and evaluated 250 children aged 3 to 5 years. As a sample, two groups were established: the normal term children group (n=125) was selected at a day-care centre and the group of preterm children (125) was identified at a public uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
(31 reference statements)
1
5
0
11
Order By: Relevance
“…Regarding breast feeding, NNSHs were less common among children who were breast‐fed at the time of hospital discharge. This finding agrees with the literature: several authors observed an association between longer duration of breast feeding and less use of pacifiers 11,13,37,43 . In addition, we found no association between NNSHs and factors such as gestational age and small for gestational age.…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding breast feeding, NNSHs were less common among children who were breast‐fed at the time of hospital discharge. This finding agrees with the literature: several authors observed an association between longer duration of breast feeding and less use of pacifiers 11,13,37,43 . In addition, we found no association between NNSHs and factors such as gestational age and small for gestational age.…”
Section: Commentsupporting
confidence: 93%
“…Apart from differences in age, these figures imply cultural differences in the frequency of NNSHs. Although comparing populations as different as those in Senegal, China, and France regarding NNSHs is difficult, a recent, albeit limited, Brazilian study conducted in a single municipality (250 children age 3 to 5 years), compared full‐term children and preterm children, finding a 54% frequency of NNSHs in full‐term children but 80% in preterm children 37 . This result is consistent with ours even though the children in our study were somewhat younger (age 2).…”
Section: Commentmentioning
confidence: 99%
“…The results, however, show a negative relationship between pacifier use and breastfeeding exclusivity, as well as primiparity, higher hospital length and higher length of orogastric tube. In addition, the retrospective cross-sectional study of Carcavalli published in 2018 [ 43 ], investigated the relationship of pacifier use between 250 children (125 preterm and 125full-term). The results of this study show that pacifier use was more prevalent among preterm infants and associated with less than six months of breastfeeding and used of formula-feeding.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results, we found a negative association between pacifier use and breastfeeding, mainly in the prospective studies [ 40 , 41 , 42 , 43 ] which investigated the long-term effect of pacifier use in infancy. On the other hand, all randomized studies [ 5 , 13 , 44 , 47 ] evaluated the short-term effect (after hospital discharge), and found a positive association, except two [ 45 , 46 ] which found a negative association.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding a premature infant can be challenging for the mother, as she needs to pump milk regularly until her child has acquired the ability to suck the breast during neonatal hospitalization [23]. Accordingly, breastfeeding rates for very premature infants are lower than for full term infants [24][25][26]. Moreover, the use of cigarettes by mothers of preterm infants may have influenced breastfeeding initiation, as maternal smoking and exposure to smoke have been shown to affect the initiation and duration of breastfeeding [27][28][29].…”
Section: Discussionmentioning
confidence: 99%